Improving the Results of Learning Ecosystem Themes Through Discovery Learning Models In Primary Schools - Annisa Hasna QA (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research is a Classroom Action Research (CAR) which consists of two cycles. The research subjects were the fifth grade students of SDN Tambakreja 09 Cilacap, Central Java with a total of 23 students. The data technique used test and non-test techniques. The assessment instrument uses items. The data analysis used in the study included a comparative descriptive technique, namely a statistical technique by comparing the scores between cycles, the mean, the minimum score, the maximum, and the proportion. The results showed that the powerpoint video media with the discovery learning model could improve student learning outcomes in Theme 5 of the 5th grade ecosystem of SDN Tambakreja 09 Cilacap, this was evidenced by the learning outcomes in cycle I, namely 6 students out of 23 students or 26% who had not completed. while 17 students out of 23 students or 74% who completed. In cycle II, there were 5 students out of 23 students who had not completed, or 22%, while 18 students out of 23 students or 78% who had completed it. With online learning using discovery learning model, student learning outcomes increased by 4% from cycle I to cycle II. The conclusion of this research is that online learning using powerpoint video media with discovery learning models can improve student learning outcomes in Theme 5 of the fifth grade ecosystem of SDN Tambakreja 09 Cilacap.